HIFZH AL-â€˜IRá¸Œ DALAM TRANSFORMASI SOSIAL MODERN (Upaya Menjadikan Hifzhu Al-â€˜Irá¸ Sebagai MaqÄshid Al-DharÅ«rÄ«y) - Husamuddin MZ, Lc., M.A. (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2019)
The old maqÄshid theory which still survives and is popular among ushuliyÅ«n, there are five known as al-dharÅ«riyyÄt al-khamsah. The discourse to add al-dharÅ«riyyÄt al-khamsah to aldharÅ«riyyÄt al-sittah or al-sab'ah and so on, has been rolled out by ushuliyÅ«n figures, although the addition received mixed responses. One of the additional discourses is to make hifzhu al â€˜irdh part of al-dharÅ«riyyÄt. Such discourse has been offered by TÄj al-din al-subki in the book jamÃ¢u al-jawÄmiâ€™, as well as At-ThÅ«fi and Al-qarÄfi, only Al-qarÄfi is not so strict. The modern figure who offered the idea back was Yusuf Al-Qaradhawi who later received a positive response from Muhammad Ahmad Al-QayatÄ« in his dissertation. Al-SyÄthibi makes hifzhu al-â€˜irdh included in the category of hifzhu al-nafs. Likewise AlGhazali and Ibn Al-Hajib did not make hifzhu al-â€˜irdh included in the category of al-dharÅ«rÄ«y. This attitude is supported by modern maqÄshid figures including Ibn â€˜Ä€syur, Ramadan Al-Buthi and Ahmad Al-Raisuni. In addition there is also a third opinion offered by Ibn Zaghibah â€˜izz Al-Din who made hifzhul al-'irdh part of dharuriyat but not in the kulliyah category but included in the juzâ€™iyyah category. The study was conducted using descriptive analysis methods, with data library research techniques (library research), the approach taken was a sociological approach. The results of the study note that: (1) the existence of times and technology that is so fast and 'radical', indirectly affect social and legal changes; (2) the existence of ikhtilÄf among ushuliyÅ«n and related modern figures to make hifzhu al-â€˜irdh as the category of al-dharÅ«riy or al-hÄjiy; (3) with the social transformation that is so fast, then the discourse makes hifzhu al-sebagaiirdh as categorical al-dharÅ«riy is a necessity.